2012
DOI: 10.1186/1471-2180-12-129
|View full text |Cite
|
Sign up to set email alerts
|

Association between cagA and vacA genotypes and pathogenesis in a Helicobacter pylori infected population from South-eastern Sweden

Abstract: BackgroundChronic gastritis, peptic ulcer disease, and gastric cancer have been shown to be related to infection with Helicobacter pylori (H. pylori). Two major virulence factors of H. pylori, CagA and VacA, have been associated with these sequelae of the infection. In this study, total DNA was isolated from gastric biopsy specimens to assess the cagA and vacA genotypes.ResultsVariations in H. pylori cagA EPIYA motifs and the mosaic structure of vacA s/m/i/d regions were analysed in 155 H. pylori-positive gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 52 publications
4
26
1
1
Order By: Relevance
“…129) The proportions of Western CagA species containing one, two, and three EPIYA-C segments are approximately 60–70%, 20–30%, and <5%, respectively. 58) In contrast to EPIYA-C, the EPIYA-D segment rarely duplicates in East Asian CagA species.…”
Section: Caga Polymorphism In Pro-oncogenic Actionmentioning
confidence: 96%
“…129) The proportions of Western CagA species containing one, two, and three EPIYA-C segments are approximately 60–70%, 20–30%, and <5%, respectively. 58) In contrast to EPIYA-C, the EPIYA-D segment rarely duplicates in East Asian CagA species.…”
Section: Caga Polymorphism In Pro-oncogenic Actionmentioning
confidence: 96%
“…The vacA gene, present in all strains, covers two different regions, the “s” region (s1 and s2) and the “m” region (m1 and m2) [7]. Another relevant marker of pathogenicity is the cagA gene, present in about 60-70% of the H. pylori strains.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings showed that two or more cagA EPIYA-C motifs are related to atrophy in gastric mucosa [19].…”
Section: Discussionmentioning
confidence: 99%
“…Vacuolating cytotoxin A (vacA), cytotoxin-associated gene A (cagA) protein, and urease enzyme are the most important virulence factors of H. pylori. Recent studies have focused on investigating the relationship between virulence factors and clinical condition [6][7][8]. CagA protein is present 60%-80% in H. pylori strains and is generally accompanied by VacA [9].…”
Section: Introductionmentioning
confidence: 99%